TNF Neutralization Results in the Delay of Transplantable Tumor Growth and Reduced MDSC Accumulation - Atretkhany, Kamar-Sulu N.; Nosenko, Maxim A.; Gogoleva, Violetta S.; Zvartsev, Ruslan V.; Qin, Zhihai; Nedospasov, Sergei A.; Drutskaya, Marina S. (Frontiers in Immunology, 2016)
Myeloid-derived suppressor cells (MDSC) represent a heterogeneous population of immature myeloid cells that under normal conditions may differentiate into mature macrophages, granulocytes and dendritic cells. However, under pathological conditions associated with inflammation, cancer or infection such differentiation is inhibited leading to immature myeloid cell expansion. Under the influence of inflammatory cytokines, these cells become MDSC, acquire immunosuppressive phenotype and accumulate in the affected tissue, as well as in the periphery. Immune suppressive activity of MDSC is partly due to upregulation of arginase 1 (Arg1), inducible nitric oxide synthase (iNOS) and anti-inflammatory cytokines, such as IL-10 and TGF-β. These suppressive factors can enhance tumor growth by repressing T-cell-mediated anti-tumor responses. TNF is a critical factor for induction, expansion and suppressive activity of MDSC. In this study we evaluated the effects of systemic TNF ablation on tumor-induced expansion of MDSC in vivo using TNF humanized (hTNF KI) mice. Both Etanercept and Infliximab treatments resulted in a delayed growth of MCA 205 fibrosarcoma in hTNF KI mice, significantly reduced tumor volume and in less accumulated MDSC in the blood three weeks after tumor cell inoculation. Thus, our study uncovers anti-tumor effects of systemic TNF ablation in vivo.